ARCHBISHOP MAGHAKIA ORMANYAN PEDAGOGUE (EDUCATION IN THE 21ST CENTURY, 2023)
On the article it presents scientific –pedsgogical heritage and activity of archbishop Maghakia Ormanyan.Here were analysed pedagogical ideas of theoretical and practical pedagog Maghakia Ormanyan, his pedagogical thoughts, which dedicated to national school and to organization of work in school. His thoughts and opinions are very actual for preparing as teachers, as students. Till nowdays this problem isn’t studied and we are the first pay attention on this theme.Studing this problem, we came to a conclusion that his example as a pedagog is very approximate and his heritage is actual till today this article dedicated to 180-th anniversary of archbishop Maghakia Ormanyan.
Keywords: pedagogical activity; pedagogical views; school studies; teacher; school inspector; method